France's Membership in Financial Action Task Force (FATF) and Financing of the Paris Terror Attacks in 2015 - Febriani, Sasyabella (Journal of Strategic and Global Studies, 2022)
France is one of founding members FATF with other G-7 countries and FATF’s headquarters location. According to FATF and Europol, France is not only known as one of low level risk countries in financing terrorism but also as EU member state with the most terror acts in 2015. This research is attempt to explain why the French counter terrorism financing policy based on FATF standards is not able to prevent the financing terrorism practices of Paris terror attacks in 2015. This research method used qualitative approach and used historical institutionalism approach to see how institutional evolution of FATF, France involvement in FATF decision, and the influence of FATF decision on France relates to countering terrorism financing. The findings and analysis of this research cover certain several things such as the historical aspects in 25 years France membership in FATF, the French characteristics, and the funding Paris terror attacks in 2015. The result of this study indicated that although France has important role in FATF, but historically, France has ignored some important things which encourage the financing activities for terrorist network.